"Timing" of arrival and in-hospital mortality in a cohort of patients under anticoagulant therapy presenting to the emergency departments with cerebral hemorrhage: A multicenter chronobiological study in Italy. (15th March 2016) - Fabbian, Fabio; Manfredini, Roberto; De Giorgi, Alfredo; Gallerani, Massimo; Cavazza, Mario; Grifoni, Stefano; Fabbri, Andrea; Cervellin, Gianfranco; Ferrari, Anna Maria; Imberti, Davide
ABSTRACT: Therapy with oral anticoagulants (OACs) is a risk factor for cerebral hemorrhage (CH). Although different studies have been undertaken to investigate the timing of the onset of major cardiovascular events, no data exist on temporal patterns of the onset of CH in subjects treated with OACs. The aim of this study is to evaluate the timing of CH in patients treated with OACs. All patients who developed CH under OACs therapy and admitted to 28 Italian Emergency Departments (EDs) between September 2011 and July 2013 were enrolled. Age, sex, time and location of the hemorrhagic lesion, type of the bleeding events (idiopathic or post-traumatic), anticoagulant therapy (warfarin or new oral anticoagulants - NOAs) and time of ED admission (i.e., hour, day, month and season) were recorded. Five hundred and seventeen patients (63.2% male aged 80 ± 7.9 yrs) with CH were involved. Warfarin was taken by 494 patients (95.6%), and NOAs by 23 (4.4%). In-hospital mortality (IHM) was recorded in 208 cases (40.2%). Cosinor analysis showed a peak of CH arrival between 12:00 and 14:00 h both in the whole population (PR 73.9%, p = 0.002) and the male subgroup (PR 65.2%, p = 0.009), whereas females showed an anticipated morning peak between 08:00 and 10:00 h (PR 65.7%, p = 0.008). A further analysis between idiopathic and post-traumatic CH confirmed the presence of a 24 h pattern with a peak between 12:00 and 14:00 h (PR 58.5%, p = 0.019) and between 08:00 and 10:00 h (PR80.1%, p < 0.001) for idiopathic events and post-traumatic hemorrhages, respectively. Moreover, a seasonal winter peak was identified for idiopathic forms (PR 74%, p = 0.035), and a summer peak for post-traumatic forms (PR 77%, p = 0.025). The present study suggests the presence of a temporal pattern of ED arrivals in CH patients treated with OACs.